The Consequence Which Operational Efficiency Makes On The Business’s Capacity To Preserve Its Financial Stability In The Banking Sector In 2022-2024 - Ratih Pratiwi Muji Lestari; Murtianingsih (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objective: Indonesia’s uncertain economic growth, coupled with obstacles such as inflation, global instability, and post-pandemic recovery, has led to an interesting dynamic in Indonesia’s financial condition for the 2022-2024 period, with stable but slightly slowing economic growth. This requires banks to manage operating costs effectively. Background: Based on previous findings, the ratio of operating expenses to operating income and non-performing loan do not significantly impact profitability and are arguably unrelated to a company’s ability to generate profits. Conversely, the cost-to-income ratio has a positive impact because it can increase a company’s capacity to generate profits. This study aims to examine how this aspect of operational efficiency affects banks’ financial condition for the 2022-2024 period. Novelty: This study measures efficiency indicators using the ratio of operating expenses to operating income, cost-to-income ratio, non-performing loan, and return on assets as profitability metrics that indicate bank stability. The study’s originality is demonstrated by the cost-to-income ratio applied to conventional banks for the 2022-2024 period. Research Methods: This study employed quantitative methods and selective sampling across 19 banks. Based on agency theory, this study uncovered the relationship between owners and management. The classical assumption test and t-test using SPSS 27 were the analytical tools used to confirm this hypothesis. Findings/Results: Based on the findings, the operating expense to operating income ratio, the cost to income ratio, and the non-performing loan ratio all had significant and unfavorable effects on profitability. Conclusion: This study indicates that operating expenses and operating income, the cost-to-income ratio, and non-performing loan impact a company’s financial stability. This study suggests that bank management should manage operating costs to maintain efficiency, improve revenue management efficiency relative to total costs, optimize non-interest income sources and asset utilization efficiency, and reduce non-performing loan by strengthening credit risk management.